1999
DOI: 10.1046/j.1365-2648.1999.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Vital signs and nurses’ choices of titrated dosages of intravenous morphine for relieving pain following cardiac surgery

Abstract: Postoperative pain, if unrelieved, will impede patients' recovery. A theoretical model of factors which influence nurses' choices of titrated dosages of intravenous (IV) morphine was constructed for this study. This study aimed to examine whether or not a patient's vital signs would influence nurses' choices of titrated dosages of IV morphine for relieving pain following cardiac surgery. A survey design with a vignette and questionnaire method was used to collect data. The vignette developed by McCaffery & Fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…6 It has also been hypothesized that in an environment where the speedy hemodynamic stabilization and reversal of anesthesia is paramount, pain control can become a secondary consideration. 2,7 Despite the common belief expressed by many nurses that cardiac surgery is not very painful 8 studies have shown that operations that necessitate a sternal incision do cause substantial pain. 9,10 Specifically, studies describe the intensity of cardiac surgical pain as fluctuating mainly between moderate to severe.…”
Section: Introductionmentioning
confidence: 99%
“…6 It has also been hypothesized that in an environment where the speedy hemodynamic stabilization and reversal of anesthesia is paramount, pain control can become a secondary consideration. 2,7 Despite the common belief expressed by many nurses that cardiac surgery is not very painful 8 studies have shown that operations that necessitate a sternal incision do cause substantial pain. 9,10 Specifically, studies describe the intensity of cardiac surgical pain as fluctuating mainly between moderate to severe.…”
Section: Introductionmentioning
confidence: 99%
“…43 Despite published guidelines and research listed previously, health care providers often use clinical data, including vital signs, when assessing pain and deciding whether to administer analgesic agents. 35,[44][45][46][47][48] According to these study results, assumptions about pain (or lack thereof), in light of normal vital signs, should not be made. Judgments regarding the need for analgesia remain subjective determinations for both patient and provider.…”
Section: Resultsmentioning
confidence: 99%
“…Smärtutvärdering är en viktig grund för en effektiv smärtlindring. Dock har studier visat att sjukvårdspersonal ofta undervärderar patienternas smärta (15,16,17,18). Denna underskattning kan bero på att vårdpersonalen inte på ett acceptabelt sätt har metoder och rutiner för en giltig smärtbedömning.…”
Section: Diskussionunclassified